Determination of Morphological Characteristics in Kuantan Cattle using Multivariate Analysis - Restu Misrianti; Jessy Mainidar; Hasrul Bani Asharudin; Yureni Sahril Dedi; Arsyadi Ali; Sony Hartono Wijaya; Cece Sumantri; Jakaria Jakaria (Faculty of Animal Science, Universitas Gadjah Mada, 2021)
The objective of this research was to characterized morphology and estimated genetic distance between intra population of Kuantan cattle. A Total of 213 cattle (44 male and 169 female with age ranging from 2-3 years) were used in this study and collected from extensive ranging systems in Three sub-population (Cerenti, Inuman, and Kuantan Hilir regions) Kuantan Singingi Regency, Riau Province. Five variables were measured that is Body Length (BL)(cm), Wither Height (WH)(cm), Hip Height (HH)(cm), Chest Girth (CG)(cm), and Chest Depth (CD)(cm). Data obtained were descriptive analysis, Principal Components Analysis (PCA) and Hierarchichal Clustering Analysis (HCA) using XLSTAT program. All variables of body measurement in the Kuantan Hilir region were higher than Cerenti dan Inuman, Kuantan Singingi Regency. The first factor in PCA described body measurement contributed 32.77%, and the second factor described body shape contribute 25.83% of total variability. The dendrogram showed there is Three clusters of Kuantan Cattle based on this research.